Historical Aspects of the Internationalisation of the Higher Education as Historical Examples of Innovation and Knowledge Transfer - Kőmíves, Péter Miklós (International Journal of Engineering and Management Sciences, 2020)
The internationalisation of the higher education is one of the most actual topics of the education management nowadays. It can bring a solution for the problems of the Hungarian higher educational institutions caused by the demographically expected decrease of the number of students. The internationalisation of the higher education is not a new-fangled phenomenon however it became much popular in the last decades and it has been spread globally. The aim of this article to show the historical aspects of the internationalisation in higher education based on literature review and research.